Study of contact sensitivity to cosmetic allergens in melasma - Sonali Verma; Rashmi Sarkar; Bijaylaxmi Sahoo (Wolters Kluwer Medknow Publications, 2021)
Introduction: Melasma is a relatively common hypermelanotic disorder characterized by symmetrical light to gray-brown macules and patches involving photoexposed areas. Multiple factors have been implicated in the etiopathogenesis, including genetic factors, UV radiation, pregnancy, oral contraceptive pills (OCPs), thyroid dysfunction, and cosmetics. However, the role of cosmetics has not been well studied in melasma patients. The present study was designed to study the contact sensitivity to cosmetic allergens in patients with melasma. Material and Methods: Thirty patients with and thirty without melasma who visited Dermatology OPD between October 2015 and March 2017 were recruited according to selection criteria and were sequentially patch and photopatched with Indian cosmetic and fragrance series. Results: The mean age of melasma patients was 32.10 ± 6.62 years with female to male ratio of 1.72:1. Sixteen (53%) patients were found to show positive reactions on patch and photopatch testing with Indian cosmetic and fragrance series. Among 32 allergens tested, 15 allergens were found eliciting positive reaction. Thiomersol was the most common contact sensitizer eliciting positive reaction in six (38%) patients, followed by cetrimide, hexamine, and sorbitan each in three patients (19%). In the control group, only one (3.3%) subject showed positive contact allergy pattern. The results were significant (P < 0.001). Conclusion: A possible consideration of the pigmented cosmetic dermatitis and cosmetic contact sensitivity is recommended in the etiologic factors of melasma especially, in nonpregnancy/lactation induced melasma or when it is not associated with hormone therapy. Contact sensitizers might also have a role in melasma that is recalcitrant to all standard therapies.